The Iron Trial - Black, Holly; Clare, Cassandra (New York : Scholastic Press, 2014)
Callum Hunt wants to fail the Iron Trial so that he can stay away from magic. However, he passes the test and now there will be more tests to come.
Keywords: Magic -- Juvenile fiction; Magic -- Fiction